Microcredit Impact On Socio-Economic Development And Women Empowerment In Low-Income Countries: Evidence From Yemen - Al-Shami, Samer Ali Hussein; Abdullah Al Mamun; Abdul Rashid, Nurulizwa; Mohammed Al-shami (MDPI, 2021)
Microcredit financing is extensively considered as an effective development method for poverty mitigation and women empowerment. Nevertheless, relevant studies reflected opposing outcomes on microfinance effects consisting of positive, zero, and negative impacts. Thus, this research investigated Al-Amal Bank’s microcredit impacts on women empowerment in Yemen, one of the poorest Middle Eastern nations. A panel dataset and primary and secondary data were gath-ered through household surveys and propensity score matching to restrict intangible variables’ possible effects. The empirical results revealed that microcredit had a significant positive effect on monthly household incomes and accumulated asset values. Although microcredit facilitated female entrepreneurship and income generation for improved household incomes and expenditure, no influence was found on female household decisions and mobility following the patriarchal system practised in many Arabian nations, including Yemen. Hence, the study finding has theoretically and practically contributed to the body of knowledge in three ways. First, a novel proof of how microcredit interactions affected several Yemeni women empowerment elements was identified. This study also provides new insight into the empowerment theory by explaining how access to microcredit influences numerous features of women’s economic and social empowerment. Lastly, social and family traditions significantly influenced female attributes and lifestyles by reflecting how communal and family rituals affected microcredit impacts on women empowerment and vice versa. Conversely, this study guides Yemeni policymakers and those from other nations on extend-ing financial services for self-development to reduce poverty and drive women empowerment ra-ther than relying on government and international agencies.